E-042 Use of Flow Diverters in Vessels less than 2.5 mm during Intracranial Aneurysm Treatment. (26th July 2014) - Puri, A; Massari, F; Hou, S; Perras, M; Brooks, C; Stout, C; Gounis, M; Wakhloo, A
Abstract : Introduction/purpose: Pipeline Embolization Device (PED) is currently indicated for treatment of large and complex intracranial aneurysms centerd along the cavernous/intradural segment of the internal carotid artery (ICA) proximal to the Posterior Communicating (PCom) artery. The purpose of this study is to assess the efficacy and safety of flow diversion treatment in unruptured complex aneurysms centerd along small vessel branches of the anterior and middle cerebral arteries. Materials and methods: From August 2013 to December 2013, a total of 3 intracranial aneurysms located along small vessel branches of the anterior circulation in 3 patients (1 man and 2 women; age range, 60–71 years; mean age, 64.6 years) were treated with pipeline embolization device (PED) at our institution. In 2 patients the aneurysms were incidentally found during cerebral angiogram exam performed for additional unruptured intracranial aneurysm treatment planning; in the other case the aneurysm was prior source of a subarachnoid haemorrhage (SAH). The parent vessel size ranged from 1.8 to 2.2 mm, mean 2 mm. Location of the aneurysms was as follows: 2 aneurysms centerd along the pericallosal artery (1 left, 1 right), branch of the anterior cerebral artery (ACA), and 1 aneurysm located on the right angular artery, branch of the middle cerebral artery (MCA). In the patient group no family history for intracranial aneurysm is reported. Aneurysms ranged from 2.5 to 3.7 mm in maximal diameter. The technical feasibility of the procedure, procedure-related complications, angiographic results, and clinical outcome were evaluated. At 6 month follow-up (1 patient) was noted a complete right angular artery aneurysm obliteration, with mild in-PED intimal hyperplasia. Results: In every case, endovascular treatment was achieved. Immediate angiography demonstrated a intra-aneurysmal contrast stagnation, with parent artery preservation. No major or minor procedure-related complications were noticed. None of the treated aneurysms experienced bleeding or thrombo-embolic complication intra-, post procedurally or on follow-up. Conclusion: Although the experience is limited by the small volume of cases treated with PED for unruptured complex aneurysms centerd along less than 2.5 mm vessel branches of the anterior circulation, the procedure was noted to be a feasible, safe and effective method to obtain aneurysm occlusion without parent vessel occlusion. Disclosures: A. Puri: None. F. Massari: None. S. Hou: None. M. Perras: None. C. Brooks: None. C. Stout: None. M. Gounis: None. A. Wakhloo: None.